Effects of hot isostatic pressing and heat treatments on structural and corrosion properties of direct metal laser sintered parts. Issue 5 (10th June 2021) - Yılmaz, Mustafa Safa; Özer, Gökhan; Öter, Zafer Çağatay; Ertuğrul, Onur
Abstract : Purpose: This paper aims to investigate the effects of various heat treatments on microstructure, hardness, porosity and corrosion properties of the parts. Design/methodology/approach: Hot isostatic pressing (HIP) process, various heat treatments and their combinations were applied to the AlSi10Mg parts produced by direct laser metal sintering (DMLS). Findings: It has been found that the HIP process, which is a post-processing process, reduces the amount of porosity in DMLS-AlSi10Mg material, thus improves corrosion resistance significantly. Originality/value: In this study, the HIP process and subsequent T6 heat treatments were applied to AlSi10Mg parts produced by the DMLS technique. The study aims to increase the corrosion resistance of AlSi10Mg parts by reducing porosity with the HIP process and by altering the microstructure with the T6 process.